Analisa Penghematan Biaya Proyek Pembangunan Rumah Susun 3 Tahun 2018 Dengan Menerapkan Value Engineering - Hengki Dermawan; Mohd. Isa T. Ibrahim; Muhammad Ridha (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Abstract: Value Engineering is a management effort in the cost analysis of a project to get the desired function that is cost efficient but does not alter or reduce the quality, functionality, and benefits of the project. The purpose of value engineering analysis in the 3-house construction project is to know the high cost work items, alternative materials that can be used, as well as calculate the initial cost comparison with the cost after applied the value engineering to know the amount of cost savings.This research uses a comparative analysis method between additional work costs and a cost worth less than 3 (Cost/Worth < 3). In the case study of the construction of this 3-piece home project The data used includes work image data, Unit price analysis list data, and budget cost plan data (RAB).From the analysis of value engineering, known items of work that have high costs are floor work, wall work, utility work, finishing work, ground tank work and pump house outside the building, work around the exterior of the building, and work facilities and environmental infrastructure. Alternative materials that can be a substitute for the initial material in the cost saving effort in the construction project 3 of the House is a brand of romance and brand Noble, closet sitting brand Toto S 516, water faucet brand Classic sus304, shower brand Fiorentino, stop faucet brand Toto, sink complet brand Toto LW 246j, paint wall avitex avian, wool yarn of corn brand, bak garbage fiber size 240 liters, paving block between + pairs (local product of the area is Blang Star). The initial cost of the 3-house project is Rp. 9,013,187,705.74,-after the application of value engineering analysis, the cost of the 3-house project to Rp. 8,711,739,049.68,-compared with the initial cost can be more efficient Rp. 301,448,656.06,-.Keywords: Value Engineering analysis, Cost/Worth, cost saving.